Minimal Accesss (TEP) versus Open Inguinal Hernioplasty: A Pragmatic Randomized Control Trial - Roy, Ratna Rani; Saha, Pankaj Kumar; Yusuf, Md Abdulla; Saha, Haridas; Hasan, Md Ibnul; Saha, Krishna Pada; Sarker, Rajib Dey (Journal of National Institute of Neurosciences Bangladesh, 2021)
Background: Inguinal hernia repair is the most frequently performed operation in general surgery. The standard method for inguinal hernia repair had changed little over a hundred years until the introduction of synthetic mesh. This mesh can be placed by either using an open approach or by using a minimal access laparoscopic technique. Objectives: The purpose of the present study was to compare minimal access laparoscopic mesh techniques with open techniques in hernioplasty. Methodology: This pragmatic randomized control trial was conducted in the Department of Surgery at Shaheed Suhrawardy Medical College & Hospital, Dhaka from January 2014 to December 2015 for a period of two years. Patients at any age with both sexes who were presented with inguinal hernia were selected as study population. These patients were divided into two group designated as group A and group B. In group A inguinal hernia repair was performed by laparoscopic technique and in group B open technique was used to repair the inguinal hernia. The comparison was done between open and laparoscopic technique of inguinal hernia repair in terms of duration of operation, per-operative complication, immediate post-operative pain, numbness, duration of hospital stay and time of return to normal activities. Follow up was done from 6 months to 2 years. Results: A total number of 200 patients were recruited for repairing of inguinal hernia. Duration of operation was longer initially in the laparoscopic groups (Laparoscopic approach 90 min vs. Lichtenstein approach 60 min). Post-operative pain was another important outcome to consider when choosing between laparoscopic and open repair of inguinal hernia. Laparoscopic repair had been associated with less post-operative pain than open repair. Operative complications were uncommon for both methods. Length of hospital stay was little shorter in laparoscopic group (laparoscopic 1-2 days vs. open technique 3-4 days); however, return to usual activity was earlier for laparoscopic groups (7 days) where open group: 20-30 days. The data available showed less persisting pain (Overall 8/80 versus 12/100) and less persisting numbness (Overall 3/80 versus 7/100) in the laparoscopic groups. Conclusions: In conclusion, minimal access laparoscopic mesh technique is better than open techniques in inguinal hernia repair. Journal of National Institute of Neurosciences Bangladesh, January 2021, Vol. 7, No. 1, pp. 75-78